2022
DOI: 10.1093/ptj/pzac028
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit–Acquired Weakness in Patients With COVID-19: Occurrence and Associated Factors

Abstract: Objective The primary objective of this study was to identify the occurrence and factors associated with intensive care unit (ICU)–acquired weakness (ICUAW) in patients with COVID-19. Secondarily, we monitored the evolution of muscle strength and mobility among patients with ICUAW and patients without ICUAW and the association of these variables with length of stay, mechanical ventilation (MV), and other clinical variables. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…However, based on studies of other ICU patient populations, there is no reason to assume that implementation of mobility interventions is any higher in individuals admitted to the ICU due to COVID-19 42,43. Based on the limited evidence for individuals with COVID-19, ICUAW continues to be concerning and prevalent in this population 10,11,17…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, based on studies of other ICU patient populations, there is no reason to assume that implementation of mobility interventions is any higher in individuals admitted to the ICU due to COVID-19 42,43. Based on the limited evidence for individuals with COVID-19, ICUAW continues to be concerning and prevalent in this population 10,11,17…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care unit acquired weakness has been correlated with increased length of ICU stay, difficulty weaning from mechanical ventilation, impaired mobility performance, diminished exercise tolerance, decreased independence with activities of daily living at discharge, and lower quality of life 8,17. A recent prospective observational study of 75 patients with COVID-19 admitted to the ICU for more than 72 hours found that bed rest time was independently associated with the development of ICUAW 11…”
mentioning
confidence: 99%
See 3 more Smart Citations